Pelatihan dan Pendampingan UMKM Najma Bucket Selempang dalam Meningkatkan Penjualan melalui Platform Marketplace Shopee - Sukma, Puja Kurnia; Rahmadanuh, Pulung Awang; Lestari, Putri Dwi; Hayomi, Putri Rindang; Nanisa, Qoirun; Shidiqy, Dhiya’u (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This service aims to help Najma Bucket Selempang MSMEs maximize product marketing through digital marketplace platforms, especially Shopee. This approach supports online marketing strategies and a deep understanding of consumer segmentation, which in turn increases business owners' knowledge and drives turnover growth. The ABCD (asset-based community development) method is implemented to ensure strong collaboration with the surrounding community. The results of the discussion show that optimizing marketing through Shopee provides significant benefits for MSMEs, makes it easier to increase sales, and opens up opportunities for market development in various regions. This program not only provides practical benefits for increasing the competitiveness of MSMEs but also provides strategic knowledge that can help them adapt and develop in the increasingly advanced digital era. Overall, this service helps strengthen the MSME ecosystem and improve the welfare of business owners and local communities.